College of American Pathologists (CAP)/American College of Medical Genetics and Genomics (ACMG) proficiency testing for urinary glycosaminoglycan analysis: A summary of performance - Kristina Cusmano-Ozog; Dietrich Matern; Thomas Long; Nicola Longo; Sarah Young (Genetics in Medicine Open)
Purpose: Glycosaminoglycans (GAGs) accumulate in patients with mucopolysaccharidoses (MPS), multiple sulfatase deficiency, and mucolipidoses; measurement of total GAGs and the specific excretion pattern by fractionation can aid in their diagnosis. Since 1993, the College of American Pathologists with the American College of Medical Genetics and Genomics has offered proficiency testing (PT) for urine GAG analysis accessible to laboratories worldwide. Methods: Data from PT surveys administered from 2016 to 2022 were assessed for trends in participation and methodological platforms used, as well as analytical performance and diagnostic accuracy by method and disease. Results: The number of participating laboratories declined from 43 in 2016 to 28 in 2022. Fourteen urine samples with clinical vignettes were distributed; the median of correct diagnoses reported was 91.5% (range: 74%-100%). The best performing methodologies for total GAG analysis and fractionation were dimethylmethylene blue-dye-binding spectrophotometric assay and liquid chromatography-tandem mass spectrometry, respectively. MPS IV samples posed the greatest diagnostic challenge, whereas the overall false-positive rate was low. Conclusion: Based on the data reviewed, best patient care for those at risk of an MPS is achieved by a combination of total GAG analysis and GAG fractionation. Development of liquid-chromatography-tandem-mass-spectrometry-based methods for quantitative, differentiated GAG analysis or disease-specific GAG-derived nonreducing end oligosaccharide fragments in combination with multiplexed lysosomal enzyme assays will likely improve diagnostic accuracy. The decline of laboratories participating in PT is concerning because MPS are increasingly included in newborn screening programs and urinary GAGs can be used to monitor the effectiveness of new therapies.